A Study of Indian College Students' Happiness and Related Factors: A Review (International Journal of Innovative Research in Engineering & Management, 2023)
India is a fascinating case study in  happiness. Because of its remarkable history, fast  economic development, huge population, and ethnic,  religious, and linguistic variety, it is a one-of-a-kind  civilization. In this chapter, we look at happiness as both  a "outside-in" and "inside-out" phenomena, and we put it  in the context of India. We examine poll data on Indians'  life satisfaction from the outside in, finding that they are  moderately happy but may grow more so if policies are  established to provide employment and infrastructure to  more people. We look at the various ways that subtle  culture influences individual happiness from the inside  out. Finally, we provide suggestions for happiness-related  treatments. The findings in this area are significant not  just for their contribution to our knowledge of human  behavior, but also for their policy implications. While  Bhutan may very well have taken a risk by coining the  phrase Using the phrase 'Gross National Happiness,' a  play on the more often used term 'Gross National  Product,' a growing number of economists are realizing  that happiness surveys might help governments make  better decisions.
Keywords: Economy; Happiness; India; National; Research